Biochemical and haematological changes during and after liver transplantation in the pig : the effect of different methods of storage and flushing solutions - Pienaar, Bastiaan Hendrik (Division of Nephrology and Hypertension, 2017)
Liver transplantation is an accepted form of treatment in advanced liver disease. The procedure qualifies as one of the most severe surgical insults that can be inflicted upon a patient. Despite an ever increasing number of clinical and experimental transplants, a vast number of unanswered questions remains about the effects of storage and transplantation per se, on the functions of this complex organ. The administration of drugs and blood, with the effects of the donor state and preservation damage obscure changes in parameters that are inherently due only to the process of transplantation, Changes in calcium and other electrolyte homeostasis, liver function assessment, acid base metabolism and coagulation defects that are seen after liver grafting, are of particular interest to transplant physicians. Current clinically employed indices of liver function, such as enzyme levels, are notoriously lacking in specificity and sensitivity, The aim of the study was to investigate in the experimental situation, the effects of standardised preservation and transplantation, without the added effects of blood transfusion or immunosuppressive drug administration, upon calcium and other electrolyte homeostasis, liver function and coagulation changes. Furthermore, reliable indicators of liver function and/or damage were looked for. It was not an investigation into preservation methods to determine superiority of one or another of these methods, but an evaluation of changes occurring utilising established and clinically proven methods of preservation. Since researchers in the J.S. Marais laboratory, as well as their international counterparts, have experienced problems in successful storage of the pig liver for periods longer than 9 hours, a storage duration of six hours was chosen for maximum reproducibility. A brief overview of liver transplantation history has been given, available literature perused and used in assessment and discussion of data obtained. Five groups of six animals were used for orthotopic liver transplantation. Two groups were autografted with a non-flushed and Ringers lactate flushed liver respectively. Two groups were allografted with livers stored in Collins and University of Wisconsin solutions respectively. A fifth group was transplanted with a liver stored for six hours by surface cooling alone, without any flushing at all. The latter method has not been described in experimental or clinical liver transplantation before. No immunosuppression was used in any animal, to eliminate the effects of hepatotoxic drugs. No blood was transfused at any point during or after the transplant. An animal survival rate in excess of 90%, for seven days or longer, was aimed for and obtained. Blood sampling was done at short intervals in the immediate postoperative period up to six hours and daily for a week. All currently used clinical parameters were determined, as well as indicators which are known, but novel in transplantation. Changes in total and ionised calcium values occurred in all groups and no explanatory mechanism could be identified. There was no correlation in changes between total and ionised calcium, nor any correlation with calcium content of preservation fluids. A reciprocal change in magnesium was identified. Acid base metabolism was markedly changed during and after the transplant. An increase in serum bicarbonate indicated survival, and a persisting metabolic alkalosis was seen in all survivors. Sodium and potassium values did not show marked changes, except for a temporary hyperkalaemia immediately following reperfusion. Serum values of liver transaminases were not found to be of value to discriminate between groups. Protein metabolism was not affected by transplantation. Glucose metabolism was markedly affected by transplantation and even more so by poor function. Early return of normal glucose metabolism indicated survival. Lactic acid metabolism was conspicuously altered during transplantation and could also be regarded as an indicator of hepatocyte function. Coagulation in this series of experiments was affected negligibly and not thought to be influenced by transplantation of a normal liver under ideal circumstances. Thus, changes in values within groups and variance between groups, if any, were described and possible mechanisms causing variation discussed. New indicators of good liver function post-transplant were identified. The conclusion was reached that the process of transplantation per se does cause major changes in electrolyte and acid-base metabolism, but that coagulation was not affected by the process of successful preservation and transplantation.